Microbial community mapping in intestinal tract of broiler chicken - Xiao, Yingping; Xiang, Yun; Zhou, Weidong; Chen, Jinggang; Li, Kaifeng; Yang, Hua (Poultry science, 2017)
Domestic chickens are valuable sources of protein associated with producing meat and eggs for humans. The gastrointestinal tract (GIT) houses a large microbial community, and these microbiota play an important role in growth and health of chickens, contributing to the enhancement of nutrient absorption and improvement of the birds' immune systems. To improve our understanding of the chicken intestinal microbial composition, microbiota inhabiting 5 different intestinal locations (duodenum, jejunum, ileum, cecum, and colon) of 42-day-old broiler chickens were detected based on 16S rRNA gene sequence analysis. As a result, 1,502,554 sequences were clustered into 796 operational taxonomic units (OTUs) at the 97% sequence similarity value and identified into 15 phyla and 288 genera. Firmicutes, Bacteroidetes, Proteobacteria, Actinobacteria, and Cyanobacteria were the major microbial groups and Firmicutes was the dominant phylum in duodenum, jejunum, ileum and colon accounting for > 60% of sequences, while Bacteroidetes was the dominant phylum in cecum (>50% of sequences), but little in the other four gut sections. At the genus level, the major microbial genera across all gut sections were Lactobacillus, Enterococcus, Bacteroides, and Corynebacterium. Lactobacillus was the predominant genus in duodenum, jejunum, and ileum (>35%), but was rarely present in cecum, and Bacteroides was the most dominant group in cecum (about 40%), but rarely present in the other 4 intestinal sections. Differences of microbial composition between the 5 intestinal locations might be a cause and consequence of gut functional differences and may also reflect host selection mediated by innate or adaptive immune responses. All these results could offer some information for the future study on the relationship between intestinal microbiota and broiler chicken growth performance as well as health.